INTERNATIONALIZATION OF SMALL MEDIUM ENTERPRISES: SUSTAINABLE STRATEGIC OF HUMAN RESOURCES DEVELOPMENT - F. Dalimunthe, Ritha; Roni Hasibuan, Fahru; Napitu, Berliana; Rifai, Arif; Qamariah, Inneke (CV. Radja Publika, 2022)
The lack of solid economic fundamentals in Indonesia has prompted the government to build an economic structure by taking into account the presence of Micro, Small and Medium Enterprises (MSMEs) in the international market. This sector has been proven to provide jobs and provide opportunities for SMEs to develop in the community. The existence of MSMEs cannot be doubted because they have proven to be able to survive and become an economic driver, especially after the economic crisis. On the other hand , SMEs also face many problems, namely limited working capital, low human resources, and incompetent mastery of science and technology (Sudaryanto and Hanim, 2002). Another obstacle faced by SMEs is the relationship with unclear business prospects and unstable planning vision and mission. Provision of information and market networks, easy access to funding and assistance as well as capacity building for information technology are some of the strategies to increase the competitiveness of Indonesian MSMEs. Therefore, it is necessary to synergize all parties, especially between the government and microfinance institutions.